Degradable plastic meal box composition and preparation method thereof

By combining polylactic acid and poly(3-hydroxybutyric acid-co-3-hydroxyvaleric acid) into the degradable plastic lunch box and adding specific ingredients and process flows, the degradable plastic lunch box in the existing technology has been solved. The problems of insufficient brittleness, heat resistance and antibacterial properties have achieved the improvement of the comprehensive performance of the materials and the guarantee of food safety.

CN119161706APending Publication Date: 2024-12-20王超
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411425102.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing biodegradable plastic lunch boxes have problems such as high brittleness, poor heat resistance, poor barrier performance, insufficient antibacterial properties and food safety hazards in the food packaging field, which are difficult to meet the actual application needs.

Method used

Acetylated monoglycerides, carboxymethylcellulose, sodium alginate, citric acid and natural Components such as β-carotene improve the toughness, heat resistance, barrier properties and antibacterial properties of the materials by adjusting the component ratio and process flow, while ensuring food safety and complete degradability.

Benefits of technology

It achieves the improvement of the excellent mechanical properties, heat resistance, barrier properties and antibacterial properties of the material, while ensuring food safety and complete degradability, meeting the safety and environmental protection requirements of food-grade applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005081922960000081
    Figure BDA0005081922960000081
Patent Text Reader

Abstract

The invention discloses a degradable plastic meal box composition and a preparation method thereof. The meal box composition comprises the following raw materials in parts by weight: 100 parts of polylactic acid; 30 to 50 parts of poly (3-hydroxybutyrate-co-3-hydroxypentanoic acid); 3 to 6 parts of acetylated monoglyceride; 2 to 4 parts of carboxymethyl cellulose; 1-3 parts of sodium alginate; 0.5 to 1 part of citric acid; 0.1 to 0.3 part of natural beta-carotene; wherein the content of 3-hydroxyvaleric acid in the poly (3-hydroxybutyrate-co-3-hydroxyvaleric acid) is 10 to 15 mol percent, and the weight-average molecular weight of the poly (3-hydroxybutyrate-co-3-hydroxyvaleric acid) is 20 to 300 thousands. Compared with the prior art, the degradable plastic film not only has excellent complete degradation performance, but also has remarkably improved heat resistance, mechanical property, barrier property and antibacterial property, and meanwhile, the food safety is ensured to be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lunch box materials, and in particular relates to a degradable plastic lunch box composition and a preparation method thereof. Background Art

[0002] With the continuous improvement of environmental protection awareness and the increasingly serious problem of plastic pollution, degradable plastics are receiving more and more attention as a substitute for traditional plastics. Among many application fields, food packaging, especially disposable lunch boxes, is one of the important application directions of degradable plastics. However, there are still many problems with the degradable plastic lunch boxes on the market, which are difficult to meet the needs of practical applications.

[0003] Polylactic acid (PLA), a biodegradable material derived from renewable resources, is widely used in the production of degradable lunch boxes due to its good biocompatibility and processability. However, PLA also has disadvantages such as high brittleness, poor heat resistance, and poor barrier properties, which seriously limit its application in the field of food packaging.

[0004] In order to improve the performance of PLA, researchers have tried many methods. For example, the toughness of PLA can be improved by adding toughening agents, but this often reduces the strength and modulus of the material. Another common method is to blend PLA with other biodegradable polymers such as polycaprolactone (PCL) or polyhydroxyalkanoate (PHA), but this method often faces the problem of poor compatibility, resulting in unstable material performance.

[0005] In addition, in order to improve the heat resistance and barrier properties of PLA-based materials, researchers have tried to add inorganic fillers such as montmorillonite or nano-silica. However, these inorganic fillers often affect the transparency and degradability of the materials and may pose safety risks in food contact applications.

[0006] In terms of improving the antibacterial properties of materials, a common method is to add silver ions or other metal ions, but these additives may migrate into food and cause food safety issues. At the same time, how to ensure the complete degradability of materials while maintaining their performance is also a difficult problem that needs to be solved urgently.

[0007] Therefore, developing a plastic lunch box composition that has excellent mechanical properties, heat resistance, barrier properties, and antibacterial properties while ensuring food safety and complete degradability has become a hot topic and difficulty in current research. Summary of the invention

[0008] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a new type of fully food-grade degradable plastic lunch box composition, which not only has excellent complete degradation performance, but also has significantly improved heat resistance, mechanical properties, barrier properties and antibacterial properties, while ensuring food safety.

[0009] In order to achieve the above object, the present invention adopts the following technical solutions:

[0010] A novel all-food-grade degradable plastic lunch box composition comprises the following raw materials in parts by weight:

[0011] Polylactic acid (PLA) 100 parts;

[0012] Poly (3-hydroxybutyric acid-co-3-hydroxyvaleric acid) (PHBV) 30-50 parts;

[0013] 3-6 parts of acetylated monoglyceride (AMG);

[0014] Carboxymethyl cellulose (CMC) 2-4 parts;

[0015] 1-3 parts of sodium alginate;

[0016] 0.5-1 part of citric acid;

[0017] Natural beta-carotene 0.1-0.3 parts;

[0018] The content of 3-hydroxyvaleric acid (3HV) in the poly (3-hydroxybutyric acid-co-3-hydroxyvaleric acid) (PHBV) is 10-15 mol%, and the weight average molecular weight is 200,000-300,000. PHBV is a biodegradable polyester produced by microbial fermentation, with good biocompatibility and degradability, and its performance can be regulated by adjusting the 3HV content.

[0019] Among them, the specific functions of each component of the composition are as follows:

[0020] 1) Combination of polylactic acid (PLA) and poly (3-hydroxybutyric acid-co-3-hydroxyvaleric acid) (PHBV): PLA provides good mechanical properties and processing properties, while PHBV improves the toughness and biodegradability of the material. The content of 3-hydroxyvaleric acid (3HV) in PHBV is 10-15 mol%, which can significantly improve the flexibility of the material while maintaining good mechanical properties. The weight-average molecular weight of PHBV is 200,000-300,000, and this molecular weight range can ensure that the material has sufficient mechanical strength while maintaining good processing properties.

[0021] 2) Acetylated monoglyceride (AMG): As a food-grade plasticizer, AMG improves the compatibility of PLA and PHBV. The addition of AMG increases the flexibility of the material and improves the processing performance. The degree of acetyl substitution is 0.5-0.7, which can maintain a good plasticizing effect without excessively reducing the mechanical strength of the material.

[0022] 3) Carboxymethyl cellulose (CMC) and sodium alginate: These two ingredients work together to significantly improve the barrier properties and water retention of the material. The degree of substitution of CMC is 0.7-0.9, and the viscosity is 400-800mPa·s, which can provide good thickening effect and film-forming properties. The M / G ratio of sodium alginate is 1.5-1.8, which can provide excellent gel strength and stability.

[0023] 4) Citric acid: As a pH regulator, it ensures the stability of the material during use. At the same time, as a nucleating agent, it increases the crystallinity of PLA, thereby improving the heat resistance of the material.

[0024] 5) Natural β-carotene: As a safe colorant, it gives the material a unique color. It also has an antioxidant effect and improves the stability of the material.

[0025] Preferably, the polylactic acid is highly crystalline poly-L-lactic acid (PLLA) with a stereoregularity greater than 98% and a number average molecular weight of 150,000-200,000, which provides higher mechanical strength and heat resistance; the molecular weight range is moderate, which ensures strength without causing processing difficulties.

[0026] Preferably, the acetyl substitution degree of acetylated monoglyceride (AMG) is 0.5-0.7. Within this range, AMG can provide the best plasticizing effect while maintaining good compatibility.

[0027] Preferably, the degree of substitution of carboxymethyl cellulose (CMC) is 0.7-0.9, and the viscosity is 400-800 mPa·s (2% aqueous solution, 25° C.) CMC in this range can provide the best thickening effect and barrier properties.

[0028] Preferably, the M / G ratio (mannuronic acid / guluronic acid ratio) of sodium alginate is 1.5-1.8. This ratio can provide optimal gel strength and stability, and further improve barrier properties.

[0029] Preferably, the citric acid is anhydrous citric acid. Compared with ordinary citric acid, anhydrous citric acid can provide a more stable pH adjustment effect while avoiding the introduction of additional water.

[0030] Preferably, natural β-carotene is extracted from carrots with a purity greater than 98%. High purity ensures better coloring effect and antioxidant properties while minimizing the introduction of impurities.

[0031] Preferably, the lunch box composition also includes 1-3 parts of citrus flavonoids and 0.5-1 parts of nisin by weight. Among them, citrus flavonoids are a powerful natural antioxidant that can synergize with beta-carotene to significantly improve the antioxidant properties of the material. Nisin is a natural antimicrobial peptide that can synergize with PLA and PHBV to provide long-lasting antibacterial properties without affecting the degradability of the material. Citrus flavonoids can also be used as natural plasticizers to synergize with AMG to improve the processing properties of the material. Therefore, the improved composition formula achieves multiple synergistic effects of antioxidant, antibacterial and plasticizing, while maintaining complete degradability and food safety.

[0032] Preferably, the lunch box composition also includes 2-4 parts of yeast β-glucan and 0.3-0.6 parts of propolis extract by weight. Among them, yeast β-glucan is a natural polysaccharide that can synergize with CMC and sodium alginate to significantly improve the barrier properties and mechanical strength of the material. Propolis extract contains a variety of flavonoids, which can synergize with β-carotene to provide strong antioxidant and antibacterial properties. β-Glucan can also be used as a compatibilizer to improve the compatibility of PLA and PHBV and improve the uniformity of the material. Therefore, the improved composition formula achieves multiple synergistic improvements in barrier properties, mechanical strength, antioxidant and antibacterial properties while maintaining good biocompatibility.

[0033] Preferably, the lunch box composition also includes 1-2 parts of carboxymethyl chitosan and 0.5-1 parts of eucalyptus extract by weight. Among them, carboxymethyl chitosan is a water-soluble derivative of chitosan, which can synergize with CMC and sodium alginate to significantly improve the barrier properties and water retention of the material. Eucalyptus extract is rich in terpenoid compounds, which can provide natural antibacterial and insect repellent effects, and cooperate with the barrier properties of the material itself to improve the preservation effect of food. Carboxymethyl chitosan can also form hydrogen bonds with PLA and PHBV to improve the compatibility and dispersibility of each component. The essential oil components in eucalyptus extract can cooperate with AMG to further improve the processing properties of the material. Therefore, the improved composition formula achieves multiple synergistic improvements in barrier properties, water retention, antibacterial properties and processing properties, while giving the material unique functional properties.

[0034] In addition, the present invention also provides a method for preparing the novel all-food-grade degradable plastic lunch box composition, comprising the following steps:

[0035] (1) Drying polylactic acid and PHBV in a vacuum oven at 70-80° C. for 6-8 hours and taking them out for later use;

[0036] (2) weighing the dried polylactic acid, PHBV and other components in proportion, adding them into a high-speed mixer and stirring at a speed of 1000-1200 rpm for 8-10 minutes;

[0037] (3) feeding the mixed materials into a twin-screw extruder with a high shear mixing section, the temperatures from the feed port to the die are 150°C, 160°C, 165°C, 170°C, and 175°C, and the screw speed is 100-120 rpm;

[0038] (4) The extruded melt is water-cooled and then pelletized to obtain the degradable plastic lunch box composition.

[0039] Preferably, the composite material particles are injection molded to obtain the final lunch box product, and the injection molding temperature is 170-180°C.

[0040] The vacuum drying step of the preparation method of the present invention ensures low moisture content of the raw materials, which is conducive to improving product quality and stability. The use of a high-speed mixer ensures uniform dispersion of the components. The twin-screw extruder with a high shear mixing section improves the dispersibility and compatibility of the components. The temperature gradient is reasonably set, which not only ensures sufficient melting and mixing of the materials, but also avoids thermal degradation.

[0041] Compared with the prior art, the present invention has at least the following beneficial effects:

[0042] (1) All raw materials in the present invention are food grade and biodegradable, fully complying with the safety and environmental requirements of food contact materials;

[0043] (2) The introduction of PHBV significantly improved the toughness and biodegradability of PLA, while also improving the heat resistance of the material;

[0044] (3) Acetylated monoglyceride (AMG) as a food-grade plasticizer improves the compatibility and processing properties of PLA and PHBV;

[0045] (4) The addition of carboxymethyl cellulose (CMC) and sodium alginate improves the barrier properties and water retention of the material, extending the shelf life of food;

[0046] (5) Citric acid not only acts as a pH regulator, but also as a nucleating agent to improve the crystallinity of PLA;

[0047] (6) Natural β-carotene acts as a safe colorant and antioxidant, giving the material a unique color and improving its stability;

[0048] (7) The use of a twin-screw extruder with a high shear mixing section improves the dispersibility and compatibility of each component;

[0049] (8) The composition of the present invention is entirely composed of food-grade biodegradable materials, which not only ensures food safety but also has excellent comprehensive performance and environmental friendliness. DETAILED DESCRIPTION

[0050] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0051] Example 1

[0052] The preparation method of the novel all-food-grade degradable plastic lunch box composition of the present invention is as follows:

[0053] 1. Raw material preparation: Dry polylactic acid (PLA) and poly (3-hydroxybutyric acid-co-3-hydroxyvaleric acid) (PHBV) in a vacuum oven at 75°C for 7 hours and take them out for use. Weigh other raw materials according to the formula requirements.

[0054] 2. Mixing: Weigh the dried PLA, PHBV and other components in proportion, add them into a high-speed mixer and stir at a speed of 1100 rpm for 9 minutes.

[0055] 3. Extrusion: put the mixed materials into a twin-screw extruder with a high shear mixing section. The temperatures from the feed inlet to the die are 150°C, 160°C, 165°C, 170°C, and 175°C, respectively, and the screw speed is 110rpm.

[0056] 4. Granulation: The extruded melt is water-cooled and then pelletized to obtain a degradable plastic lunch box composition.

[0057] 5. Injection molding: The composite material particles are injection molded to obtain the final lunch box product, and the injection molding temperature is 175°C.

[0058] The preparation methods of Examples 2 to 3 and Comparative Examples 1 to 2 are the same as that of Example 1, except for the formulation composition, as shown in Table 1 below (unit: parts by weight).

[0059] Table 1

[0060] raw material Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 PLA 100 100 100 100 100 PHBV 40 40 40 40 - AMG 4 4 4 4 4 CMC 3 3 3 3 3 Sodium alginate 2 2 2 2 2 Citric Acid 0.8 0.8 0.8 0.8 0.8 Beta-carotene 0.2 0.2 0.2 0.2 0.2 Citrus flavonoids 2 - - - - Nisin 0.8 - - - - Yeast β-glucan - 3 - - - Propolis Extract - 0.5 - - - Carboxymethyl chitosan - - 1.5 - - Eucalyptus Extract - - 0.8 - -

[0061] The following performance tests were performed on the lunch box compositions of the embodiments and comparative examples, respectively. The experimental test results are shown in Table 2.

[0062] 1. Mechanical properties: According to GB / T 1040.2-2006 standard, use a universal testing machine to test the tensile strength and elongation at break.

[0063] 2. Heat resistance: According to GB / T 1634.2-2004 standard, test the Vicat softening point.

[0064] 3. Barrier performance: Test oxygen transmission rate according to GB / T 1037-1988 standard.

[0065] 4. Antibacterial performance: According to GB / T 21866-2008 standard, the antibacterial rate against Escherichia coli was tested.

[0066] 5. Degradation performance: According to GB / T 19277.1-2011 standard, the mass loss rate under composting conditions for 60 days was tested.

[0067] Table 2

[0068]

[0069] Among them, the analysis of the above experimental test results is as follows:

[0070] 1. Comparative analysis between the embodiments and the comparative examples:

[0071] Compared with Comparative Examples 1-2, Examples 1-3 have significantly improved performance indicators, which are mainly attributed to the synergistic effect of the newly added functional components (such as citrus flavonoids, nisin, yeast β-glucan, etc.) and the original components. In particular, the performance indicators of Comparative Example 2 (without PHBV) are significantly lower than those of other formulations, indicating that the introduction of PHBV plays a key role in improving the comprehensive performance of PLA.

[0072] 2. Comparative analysis between various embodiments:

[0073] Although different functional additives are used in Examples 1-3, the overall performance is similar, and each has its own characteristics:

[0074] 1) Example 1 performed best in terms of antibacterial performance, which may be due to the special antibacterial effect of nisin.

[0075] 2) Example 2 is slightly better in terms of mechanical properties and barrier properties, which may be due to the reinforcing and barrier effects of yeast β-glucan.

[0076] 3) Example 3 performed best in terms of elongation at break, which may be due to the toughening effect of carboxymethyl chitosan.

[0077] In summary, the new all-food-grade degradable plastic lunch box composition provided by the present invention has significant advantages over traditional formulas, and has obvious improvements in mechanical properties, heat resistance, barrier properties, antibacterial properties and degradation properties. The introduction of PHBV plays a key role in improving the comprehensive performance of PLA and is an important component of this composition. The introduction of different functional additives can improve certain specific properties of the material in a targeted manner, providing flexible choices for different application scenarios. The composition of the present invention not only ensures food safety and degradability, but also achieves a comprehensive improvement in performance, providing a new solution for the development of degradable plastic lunch boxes.

[0078] It should be noted that the contents not described in detail in this specification belong to the prior art known to professional and technical personnel in the field and will not be repeated here.

[0079] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A degradable plastic lunch box composition, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of polylactic acid; Poly (3-hydroxybutyric acid-co-3-hydroxyvaleric acid) 30-50 parts; 3-6 parts of acetylated monoglyceride; 2-4 parts of carboxymethyl cellulose; 1-3 parts of sodium alginate; 0.5-1 part of citric acid; Natural beta-carotene 0.1-0.3 parts; The content of 3-hydroxyvaleric acid in the poly (3-hydroxybutyric acid-co-3-hydroxyvaleric acid) is 10-15 mol%, and the weight average molecular weight is 200,000-300,000.

2. The degradable plastic lunch box composition according to claim 1, characterized in that: The polylactic acid is a highly crystalline poly-L-lactic acid with a stereoregularity greater than 98% and a number average molecular weight of 150,000 to 200,000.

3. The degradable plastic lunch box composition according to claim 1, characterized in that: The acetylated monoglyceride has an acetyl substitution degree of 0.5-0.

7.

4. The degradable plastic lunch box composition according to claim 1, characterized in that: The degree of substitution of the carboxymethyl cellulose is 0.7-0.9, and the viscosity is 400-800 mPa·s.

5. The degradable plastic lunch box composition according to claim 1, characterized in that: The M / G ratio of the sodium alginate is 1.5-1.

8.

6. The degradable plastic lunch box composition according to claim 1, characterized in that: The citric acid is anhydrous citric acid; the natural beta-carotene is extracted from carrots, and the purity is greater than 98%.

7. The degradable plastic lunch box composition according to claim 1, characterized in that: The invention also comprises 1-3 parts of citrus flavonoids and 0.5-1 part of nisin by weight.

8. The degradable plastic lunch box composition according to claim 1, characterized in that: The invention also comprises 2-4 parts of yeast beta-glucan and 0.3-0.6 parts of propolis extract by weight.

9. The degradable plastic lunch box composition according to claim 1, characterized in that: The invention also comprises 1-2 parts of carboxymethyl chitosan and 0.5-1 parts of eucalyptus leaf extract by weight.

10. A method for preparing the degradable plastic lunch box composition according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) drying polylactic acid and poly (3-hydroxybutyric acid-co-3-hydroxyvaleric acid) in a vacuum oven at 70-80° C. for 6-8 hours and taking them out for later use; 2) weighing the dried polylactic acid, poly (3-hydroxybutyric acid-co-3-hydroxyvaleric acid) and other components in proportion, adding them into a high-speed mixer and stirring at a speed of 1000-1200 rpm for 8-10 minutes; 3) The mixed materials are fed into a twin-screw extruder with a high shear mixing section, the temperatures from the feed port to the die are 150°C, 160°C, 165°C, 170°C, 175°C, and the screw speed is 100-120rpm; 4) The extruded melt is water-cooled and then pelletized to obtain the degradable plastic lunch box composition.

Citation Information

Patent Citations

  • Polymeric blend containing poly alpha-1,3-glucan

    CN107406524A

  • High-mechanical strength and biodegradable PLA-PHBV composite material, preparation method thereof and thin film

    CN109593333A

  • Biodegradable straw and preparation method thereof

    CN111040398A

  • High-barrier antibacterial biodegradable material as well as preparation method and application thereof

    CN115536999A